Peripheral Pathways to Neurovascular Unit Dysfunction, Cognitive Impairment, and Alzheimer’s Disease - Nelson, Amy R. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common form of dementia. It was first described more than a century ago, and scientists are acquiring new data and learning novel information about the disease every day. Although there are nuances and details continuously being unraveled, many key players were identified in the early 1900’s by Dr. Oskar Fischer and Dr. Alois Alzheimer, including amyloid-beta (Aβ), tau, vascular abnormalities, gliosis, and a possible role of infections. More recently, there has been growing interest in and appreciation for neurovascular unit dysfunction that occurs early in mild cognitive impairment (MCI) before and independent of Aβ and tau brain accumulation. In the last decade, evidence that Aβ and tau oligomers are antimicrobial peptides generated in response to infection has expanded our knowledge and challenged preconceived notions. The concept that pathogenic germs cause infections generating an innate immune response (e.g., Aβ and tau produced by peripheral organs) that is associated with incident dementia is worthwhile considering in the context of sporadic AD with an unknown root cause. Therefore, the peripheral amyloid hypothesis to cognitive impairment and AD is proposed and remains to be vetted by future research. Meanwhile, humans remain complex variable organisms with individual risk factors that define their immune status, neurovascular function, and neuronal plasticity. In this focused review, the idea that infections and organ dysfunction contribute to Alzheimer’s disease, through the generation of peripheral amyloids and/or neurovascular unit dysfunction will be explored and discussed. Ultimately, many questions remain to be answered and critical areas of future exploration are highlighted.